Controlling the cascade of corona - Azmat, Muneeba (Open Science Journal, 2020)
The pandemic of the 2019 novel Coronavirus has seen unprecedented exponential growth. Within three months, 192 countries have been affected, crossing more than 1 million confirmed cases and over 60 thousand deaths until the first week of April. Decision making in such a pandemic becomes difficult due to limited data on the nature of the disease and its propagation, course, prevention, and treatment. The pandemic response has varied from country to country and has resulted in a heterogeneous timeline for novel Coronavirus propagation. We compared the public health measures taken by various countries and the potential impact on the spread. We studied 6 countries including China, Italy, South Korea, Singapore, United Kingdom(UK), United States(US), and the special administrative region of Hong Kong. All articles, press releases, and websites of government entities published over a five-month period were included. A comparison of the date of the first diagnosed case, the spread of disease, and time since the first case and major public health policy implemented for prevention and containment and current cases was done. An emphasis on early and aggressive border restriction and surveillance of travelers from infected areas, use of information technology, and social distancing is necessary for control of the novel pandemic. Moving forwards, improvement in infrastructure, and adequate preparedness for pandemics is required.